3D printed carbon-ceramic structures for enhancing photocatalytic properties. Issue 12 (15th August 2019) - Mei, Hui; Huang, Weizhao; Liu, Hongxia; Pan, Longkai; Cheng, Laifei
Abstract: 3D printing creates structures from digitally designed models by bottom-up fabrication method, achieving excellent control of target structures from various materials. Compared with conventional manufacturing methods such as machining, chemical engineering and bio-template, 3D printing shows advantages in aspects of parameterization-designed structure, rapid preparation, high precision and low cost. Herein, 3D printed carbon-ceramic support with designed array patterns, square, circular and diamond, was fabricated in an inert atmosphere to obtain sophisticated pore structure with high surface area. The existence of pyrolyzed carbon from UV-curable resin suppressed the mass transfer process when sintering and was found to greatly increase pore area from 0.067 m 2 /g to 0.509 m 2 /g. Molybdenum disulfide (MoS2 ) chosen as a typical catalyst was loaded on the sintered support. The photodegradation efficiency of as-printed carbon support with MoS2 increased to 45.95% while that of pure MoS2 was only 23.35%. The catalyst-support system showed significant stability and the efficiency decreased to 82.35% after five cycles. UV–Vis diffused reflectance spectra proved that pyrolyzed carbon increased the light adsorption efficiency at the whole range of visible light.